2021
DOI: 10.3390/molecules26113106
|View full text |Cite
|
Sign up to set email alerts
|

How to Obtain the Maximum Properties Flexibility of 3D Printed Ketoprofen Tablets Using Only One Drug-Loaded Filament?

Abstract: The flexibility of dose and dosage forms makes 3D printing a very interesting tool for personalized medicine, with fused deposition modeling being the most promising and intensively developed method. In our research, we analyzed how various types of disintegrants and drug loading in poly(vinyl alcohol)-based filaments affect their mechanical properties and printability. We also assessed the effect of drug dosage and tablet spatial structure on the dissolution profiles. Given that the development of a method th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Specifically, the use of PVPP led to an increase in the drug release rate, whereas it decreased for tablets containing CSSNa ( Figure 6 C,D). This is consistent with a previous study showing that CSSNa can indeed be less effective in enhancing the drug release from PVA-based printed tablets within a four-hour dissolution interval when compared to PVPP [ 38 ]. This behaviour can be attributed to differences in the disintegration mechanism between CSSNa and PVPP.…”
Section: Resultssupporting
confidence: 93%
“…Specifically, the use of PVPP led to an increase in the drug release rate, whereas it decreased for tablets containing CSSNa ( Figure 6 C,D). This is consistent with a previous study showing that CSSNa can indeed be less effective in enhancing the drug release from PVA-based printed tablets within a four-hour dissolution interval when compared to PVPP [ 38 ]. This behaviour can be attributed to differences in the disintegration mechanism between CSSNa and PVPP.…”
Section: Resultssupporting
confidence: 93%
“…We have shown in our previous work that the filaments with Young modulus values ranging from ca. 400 MPa up to more than 2100 MPa are printable in our set-up [22]. The DOM + M filament was 2-times more elastic in comparison to the filament without mannitol.…”
Section: Processability Of Hme Drug Content and Texture Analysis Of F...mentioning
confidence: 83%
“…The thermograms of raw materials are presented in the Supplementary Materials. We used crospovidone (PVP CL, Kollidon ® CL) as a superdisintegrant in all formulations as we have previously proven its efficiency in 3D printing technology [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, at low infill density there is less deposition of the material which results in the formation of more porous tablet leading to faster release of the drug. On the contrary, increase in infill density will increase deposition of the material which will result in less porous tablet with slow release of the drug [ 60 ]. Among all the formulation, the F2 formulation was chosen for in vivo studies as it showed the highest floating capacity with sustained release of the drug.…”
Section: Resultsmentioning
confidence: 99%